Effects of teachers’ rapport-building strategies on EFL learners’ cognitive load and computer-assisted language learning motivation - Kang, Huan; Chen, Hong (Education and information technologies, 2025)
This study investigates the effects of online instructors' use of initiation and maintenance rapport-building strategies (RBS) on Chinese EFL learners' CALL motivation and cognitive load management. Mixed methods research was used to concurrently triangulate different strands of data on the effects of RBS on 86 randomly sampled EFL learners. The interpretations were made based on methodological triangulation of QUAN + QUAL data and running one-way ANOVA. The results show that the interactive use of initiation and maintenance RBS is statistically significant in enhancing CALL motivation (F(1,84) = 23.45, p < .001) and lowering cognitive load (F(1,84) = 17.89, p < .001) compared to isolated use of these strategies. The study reveals that teachers' interactive use of RBS enhances learners' CALL motivation by increasing learning interests (mean difference = 1.98, p < .001), catering to dynamic motivational needs (mean difference = 1.64, p < .001), and creating a learner-friendly environment (mean difference = 1.42, p < .001). Moreover, the study confirms the psychological effects of interactive use of RBS in lowering cognitive load through information-sharing (mean difference = 1.89, p < .001), common-grounding (mean difference = 1.56, p < .001), and personalized instruction strategies (mean difference = 1.34, p < .001) during the CALL course. The implications of the study inform researchers and practitioners of CALL about the efficacy of using a static and flexible combination of initiation and maintenance RBS to enhance EFL learners' motivation and cognitive load.